Dynamics of Two-Body Systems - Choudhary, Twisha (Journal of Research in Science and Engineering, 2026)
This study presents a comprehensive analysis of the two-body central-interaction problem in quantum mechanics. We investigate the Schrödinger equation for two particles interacting through a central potential, and derive the radial and angular parts of the wave function. The energy eigenvalues and Eigen functions are obtained for various central potentials, including the Coulomb, harmonic oscillator, and square well potentials.